Fast-food consumption and child body mass index in China: Application of an endogenous switching regression model - Wisdom Akpalu; Xu Zhang (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
The rapid economic growth experienced within the past two decades in China highly correlates with childhood overweightness. The epidemic has become an issue of grave concern. A principal factor considered to be responsible for the epidemic in the literature is unhealthy food intake, such as fast-food consumption. This paper has found a positive impact of fast-food consumption on children's body mass index. In addition to our finding of different characteristics between children who eat fast food and those who do not, we also found that the impact of fastfood consumption on body mass index is different among the children in each of the two groups.
Keywords: C01; C21; I15; 330; child body mass index; fast-food consumption; endogenous switching regression model